Changes in measures to increase sports with medal potential: A case study of a targeted sports project - Yamashita, S. (Journal of High Performance Sport, 2022)
With the decision to host the 2020 Olympics in Tokyo, several projects were launched as measures to achieve fifth place in the ranking of the number of gold medals won in this competition. As part of these measures, a targeted sports project was implemented to increase the number of sports in which medals can be won by implementing the PDCA cycle and building a new system to develop athletes` performance. The historical development of this project is reviewed in this paper, and its prospects are also discussed. This project was designed using a structure that aims to increase the number of athletes with the potential to win medals as well as develop medal-winning sports. A further goal was to create a new performance enhancement system through activities that build a PDCA cycle for the target sports that were selected through evidence-based analysis. A review of this project shows that it was implemented in conjunction with a variety of policies and measures. In the future, the results of this project should also be taken into account for evaluation and verification. Although we have been aiming to build a new system using the PDCA cycle, it is also necessary to consider a system that can be adapted to the environment of high-performance sports while considering the limitations of the PDCA cycle.